2021
DOI: 10.1021/acsami.1c12617
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Chitosan-Gum Arabic-Coated Bipolymeric Nanocarriers for Efficient Dye Removal and Eradication of the Plant Pathogen Botrytis cinerea

Abstract: The treatment of textile wastewater comprising many dyes as contaminants endures an essential task for environmental remediation. In addition, combating antifungal multidrug resistance (MDR) is an intimidating task, specifically owing to the limited options of alternative drugs with multitarget drug mechanisms. Incorporating natural polymeric biomaterials for drug delivery provides desirable properties for drug molecules, effectively eradicating MDR fungal growth. The current study fabricated the bipolymeric d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…Other studies were carried out to test biopolymeric drug delivery systems against B. cinerea . In a recent work, Raj and collaborators 31 showed that chitosan-arabic gum-coated liposome 5I-1H-indole nanoparticles were potent inhibitors against B. cinerea growth. Up to now, despite B. cinerea causing significant damage to agriculture every year, few data are available on its uptake of PLGA NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies were carried out to test biopolymeric drug delivery systems against B. cinerea . In a recent work, Raj and collaborators 31 showed that chitosan-arabic gum-coated liposome 5I-1H-indole nanoparticles were potent inhibitors against B. cinerea growth. Up to now, despite B. cinerea causing significant damage to agriculture every year, few data are available on its uptake of PLGA NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Chemically, it is linear homopolysaccharide, composed of β-D-glucopyranose units that remain linked by β-1,4 glycosidic bonds. Apart from being the most important structural component of the primary cell wall of green plants, cellulose is found to also be present in bacteria [ 1 , 2 , 3 ]. Cellulose is a group of carbohydrates that contains considerable amounts of hydroxyl groups that remain existent in the form of polymer chain [ 4 ] and has wide applications in pulp and paper and pharmaceutical industries and as a renewable fuel source.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose nanomaterials (CNs) hold many interesting properties, for example, high mechanical strength, reinforcing capabilities, biodegradable, environmentally friendly, and self-assembly in aqueous media which arises from its tunable shape, size, surface chemistry [1][2][3][4][5][6][7][8][9]. CNs can be considered as one type of natural polysaccharides that are widely used as nanocarriers to effectively remove dyes [10] or in the pharmaceutical field as drug delivery [11]. Innovative technology and applications utilizing cellulose nanomaterials, for example, in antimicrobial materials, heavy metals, and dyes and adsorbents, have attracted tremendous efforts during the past few decades [2][3][4]6,12].…”
Section: Introductionmentioning
confidence: 99%